Landscape practices and everyday life in domestic spaces in Bronze Age Mallorca (Balearic Islands): Perspectives for and archaeology of fuel and firewood. (28th February 2017) - Picornell-Gelabert, Llorenç; Servera-Vives, Gabriel
Abstract: With this article we intend to explore a theoretical and methodological approach to energy procurement and consumption in prehistoric households through the archaeological record. To do so, we focus on a specific kind of archaeobotanical material, charred wood, and in a specific case study, the Bronze Age Naviform society of the Balearic Islands. We discuss different theoretical issues related to the study of energy consumption as socio-environmental arena of nature–culture interaction and apply the classic methodologies developed by the anthracological discipline (taphonomic interrogation of the samples and taxonomical identification) to approach the landscape practices related to firewood gathering and consumption in the megalithic Naviform households (so-called navetiforms). We present data from three of these structures in two different sites from the South of Mallorca. These datasets reveals a mosaic landscape in which the Naviform groups organized the firewood procurement in relation to their taskscape and landscape perception and organization. Sclerophyll and open vegetal formations dominated the landscape and provided the main energetic resources to the Naviform households. The cyclopean navetiforms constituted the locus in which the social life of the familiar group inhabiting them was organized and, it is in this context that the firewood practices revealed in the anthracological record can be interpreted.